Perbandingan Pelindungan Hukum Nasional dan Hukum Internasional dalam Melindungi Pekerja Migran Indonesia - Dhika Tabrozi; Prista Kelana Saeful Rohman (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2025)
The focus of this research examines the comparion of the protection of national law and international law in protecting Indonesian Migrant Workers. In national law, contained in Law Number 18 Year 2017, the state provides protection for migrant workers consisting of legal protection, social protection, and economic protection. Meanwhile, international legal protection is contained in the ILO (International Labor Organization) convention which emphasizes justice for workers. The Indonesian government has ratified 19 ILO conventions, consisting of 8 basic conventions, 2 gouvernance and 9 general or technical conventions. The research method used is normative research through legal interpretation from juridicial-normative and conceptual aspects. The approach method is carried out by comparing national law and international law as a research analysis. The research data sources used primary data and secondary data. Primary data used is the 1945 Constitution, Law No. 18/2017 on PMI, and ILO (International Labor Organization) Conventions. Data analysis techniques through legal interpretation of primary and secondary used. The results found that nastional and international laws have a correlation in protecting the rights of PMI normatively and empirically in guaranteeing the human rights of PMI. However, weak law enforcement and government supervision on the implementation of PMI indicate serious challenges in preventing the emergence of illegal Indonesian Migrant Worker Placement Company.